Two new species of Strandesia Stuhlmann, 1888 (Crustacea: Ostracoda) from Thailand, with first record of a male S. martensi Savatenalinton, 2015 - Savatenalinton, Sukonthip (European Journal of Taxonomy, 2024)
Two new species of Strandesia Stuhlmann, 1888 are described from the northeastern part of Thailand: S. karanovicae sp. nov. and S. amnatcharoenensis sp. nov. Strandesia karanovicae is characterized by a tumid carapace in dorsal view, a small anterior overlap, the absence of a dorso-subapical seta on the first segment of the antennule (A1), a large aesthetasc Y on the antenna, an α seta shape with a needle-like tip and a large β seta on the mandibular palp (Md-palp), serrated bristles on the maxilla, a long h1 seta on the second thoracopod (T2) and a slender caudal ramus (CR). Strandesia amnatcharoenensis has a small compressed posterior part of the right valves (RV) which makes it closely related to S. pholpunthini Savatenalinton, 2015. The new species can be distinguished primarily by a considerably small anterior overlap of the left valve over the right valve (RV), a postero-ventral flange of the RV, a remarkably large claw Ga of the CR and the chaetotaxy of the limbs, especially A1, Md-palp and T2. In addition, in the present study, the sexual population of S. martensi Savatenalinton, 2015 is recorded for the first time, and thus the first description of the male is provided here. Moreover, the morphological examination of both males and females revealed differences between asexual and sexual females and also points to the fact that S. martensi is a mixed reproduction species. This is the first record of the mixed reproductive mode in the genus Strandesia or even in the Cypricercinae.